Molecular mechanism of the tree shrew’s insensitivity to spiciness - Han, Yalan; Li, Bowen; Yin, Ting-Ting; Xu, Cheng; Ombati, Rose; Luo, Lei; Xia, Yujie; Xu, Lizhen; Zheng, Jie; Zhang, Yaping; Yang, Fan; Wang, Guo-Dong; et al. (PLOS Biology, 2018)
Spicy foods elicit a pungent or hot and painful sensation that repels almost all mammals. Here, we observe that the tree shrew (Tupaia belangeri chinensis), which possesses a close relationship with primates and can directly and actively consume spicy plants. Our genomic and functional analyses reveal that a single point mutation in the tree shrew’s transient receptor potential vanilloid type-1 (TRPV1) ion channel (tsV1) lowers its sensitivity to capsaicinoids, which enables the unique feeding behavior of tree shrews with regards to pungent plants. We show that strong selection for this residue in tsV1 might be driven by Piper boehmeriaefolium, a spicy plant that geographically overlaps with the tree shrew and produces Cap2, a capsaicin analog, in abundance. We propose that the mutation in tsV1 is a part of evolutionary adaptation that enables the tree shrew to tolerate pungency, thus widening the range of its diet for better survival.